2019
DOI: 10.17161/kjm.v12i4.13260
|View full text |Cite
|
Sign up to set email alerts
|

Patient’s Knowledge and Use of Oral Non-Steroidal Anti-Inflammatory Drugs in a Rheumatology Clinic

Abstract: Introduction We evaluated the knowledge of non-steroidal antiinflammatorydrugs (NSAIDs) including their dosage, side effects,contraindications, and drug interactions among the patients in anoutpatient rheumatology clinic. Methods Patients in a rheumatology clinic completed a short surveyassessing their knowledge of over-the-counter NSAIDs. Results The survey was provided to 400 participants and 275(68.5%) were using over-the-counter (OTC) NSAIDs. The majorityof the participants id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 16 publications
1
11
1
Order By: Relevance
“…In this sense, we can say that illiterate consumers in Brazil have no power of choice at the point of purchase when buying an OTC drug and can be considered “at-risk consumers” as argued by Pechmann et al (2011). Also, these results complement the findings of previous studies conducted in Europe (Sørensen et al , 2015) and the USA (Arain et al , 2019) and reinforce the findings of previous research conducted in developing countries such as South Africa (Kapp et al , 2020) and Saudi Arabia (AbuAlreesh and Alburikan, 2019).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…In this sense, we can say that illiterate consumers in Brazil have no power of choice at the point of purchase when buying an OTC drug and can be considered “at-risk consumers” as argued by Pechmann et al (2011). Also, these results complement the findings of previous studies conducted in Europe (Sørensen et al , 2015) and the USA (Arain et al , 2019) and reinforce the findings of previous research conducted in developing countries such as South Africa (Kapp et al , 2020) and Saudi Arabia (AbuAlreesh and Alburikan, 2019).…”
Section: Discussionsupporting
confidence: 84%
“…The use of these medications is a concern in both developed and developing countries. In a study conducted in the USA with 400 participants to evaluate their knowledge of OTC anti-inflammatory drugs, the authors found that almost a third of the them were unaware of the contraindication of the medication, that more than 50% denied having any discussion of OTC medications with their providers and that two-thirds of the respondents reported seeing only the medication packaging for determining the dose (Arain et al , 2019). However, direct-to-consumer (DTC) advertising usually does not provide enough information about therapeutic alternatives, efficacy, costs and risks, and the OTC drug label is the primary means through which instructions for safe and effective use are conveyed to consumers (Cohen et al , 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, analgesics can lead to side effects that affect the health of the consumer. In the aforementioned study, one third of the population was unaware of contraindications associated with analgesics [ 24 ]. After analgesics, antitussives and common cold drugs were most commonly consumed by our subjects, which is different to the results published by other authors, who reported that analgesics are the most consumed, followed by antipyretics and antibiotics [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…One of these factors could be the lack of knowledge in NSAID users about their AEs and contraindications. In a study of over-the-counter (OTC) NSAID users surveyed at a rheumatology clinic, one-third were unaware of their contraindications [ 41 ]. Similar reports of the lack of patient knowledge about NSAIDs-related AEs have been published as well [ 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%